Marine Macrobenthos of NorthWest India-Reviewing the Known and Unknown - Sukumaran, Soniya; Vijapure, Tejal; Mulik, Jyoti; Ridha, Hurmine (Frontiers in Marine Science, 2021)
Tropical ecosystems sustain higher biodiversity and face faster species extinction. However, baseline information of these areas is either inadequate or scattered due to various reasons. The 2360 km long coast of North West India (NWI), is a heavily industrialized and urbanized zone. This coast with unique biogeographical and climatic features with two notified marine protected areas also supports rich biodiversity. This review was motivated by a need to construct a synoptic view on marine benthic ecology and functioning by consolidating available information of macrobenthos. 2078 macrobenthic taxa belonging to 14 phyla were compiled from 147 references and were composed mostly by Polychaeta (n=617), Gastropoda (n=602) and Bivalvia (n=216). Habitat wise, intertidal and subtidal zones were more intensely studied and contributed most to the diversity records. Sediment texture and salinity were the major drivers of macrobenthic community structure in the subtidal areas and estuaries respectively. In the intertidal zones, zonation patterns related to the tidal levels and time of exposure were distinct with the high water zones being sparsely populated and lower intertidal zones sustaining higher species and functional diversities. All zones of NWI coast were distinctly impacted to various extent by anthropogenic activities affecting the resident macrobenthos. Decline in species richness and species substitution due to pollution were reported in urbanised zones. Non-monsoonal months favored a more conducive environment for the macrobenthic diversity and functionality. Hypoxia tolerant polychaete species mainly belonging to Spionidae and Cossuridae dominated during the low oxygen conditions of upwelling and OMZ zones of NWI. Inadequate identification and inconsistency of sampling methods were major deterrents for concluding trends of distributions. Suggestions for future macrobenthic research include focusing on lesser studied groups and areas, seasonal as well anthropogenic hypoxic zones and well planned long -term monitoring studies. Major data lacunae were identified in the taxonomy, molecular, functional aspects and bioinvasive studies of macrobenthos in this geographical zone despite clear evidence of high diversity of extant macrofauna. This compendium should help prioritize research areas and objectives aimed at enhancing our understanding of macrobenthos and improve predictive capabilities of community shifts that may occur due to global climate change scenarios.